Comparisons and References: What Can Chinese and the US Prosecutors Learn from Each Other? - Jiabo Lv (Studies in Law and Justice, 2024)
With the rapid development of the economic society, prosecutors from both China and the United States have problems that troubles themselves. For Chinese prosecutors, they are in “the era of minor crimes” in social governance, and their power seems to be limited, making it difficult to make appropriate judgments regarding individual situations. For the US prosecutors, they are not trusted due to their wide discretion and are even seen as “Leviathans” in the criminal justice system. Through comparative research, it can be found that Chinese and the US prosecutors have a broad space for mutual learning and reference. China can moderately relax the restrictions on the discretion of prosecutors and establish pre-trial diversion plans to prevent minor criminals from being punished. The United States can reform its selection system by using fair exams to prevent prosecutors from being influenced by political tendencies, racism, and other factors, so that the prosecutors can exercise their power more focused and trusted.